Morchella importuna Flavones Improve Intestinal Integrity in Dextran Sulfate Sodium-Challenged Mice - Xu, Yingyin; Xie, Liyuan; Tang, Jie; He, Xiaolan; Zhang, Zhiyuan; Chen, Ying; Zhou, Jie; Gan, Bingcheng; Peng, Weihong (Frontiers in Microbiology, 2021)
Morchella importuna, as an edible fungus, has various health benefits. However, the effects of M. importuna on intestinal health are rarely investigated. Hence, this study aims to ascertain the influences of flavones from the fruiting bodies of M. importuna (hereinafter abbreviated as MIF) on dextran sulfate sodium (DSS)-induced damage to intestinal epithelial barrier in C57BL/6J mice. In this (14-day) study, 144 C57BL/6J mice were divided into four groups: (1) Control; (2) DSS treatment; (3) DSS treatment + 100 mg/kg MIF (LMIF); (4) DSS treatment + 200 mg/kg MIF (HMIF). On days 8-14, mice in the challenged groups were challenged with 3.5% DSS, while the control group received an equal volume of normal saline. Then, serum and intestinal samples were obtained from all mice. The results showed that MIF ingestion enhanced intestinal integrity in DSS-challenged mice, as evinced by the elevated (p < 0.05) abundances of occludin, claudin-1, and zonula occludens-1 proteins. Meanwhile, MIF ingestion reduced (p < 0.05) the colonic interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), and interferon-γ (IFN-γ) concentrations and increased the superoxide dismutase and catalase activities and Shannon and Simpson indices in DSS-challenged mice. Moreover, MIF ingestion reduced (p < 0.05) the abundance of phospho-nuclear factor (NF)-κB and increased the abundance of phospho-Nrf2 in DSS-challenged mice. Taken together, MIF protects against intestinal barrier injury in C57BL/6J mice via a mechanism that involves inhibiting NF-κB activation and promoting Nrf2 activation, as well as regulating intestinal microbiota.